Putusan Terkait Sengketa Hak Atas Tanah Warisan - Pieris, Flourensya Lyventriz; Latupono, Barzah; Uktolseja, Novyta (Faculty of Law Universitas Pattimura, 2025)
Land disputes are unavoidable in today's era, this is due to the various very high land needs while the number of land plots is limited. Land dispute resolution is an effort to resolve land disputes between parties who feel disadvantaged. sIn accordance with the problems raised, the type of research used in this paper is normative legal research. Legal research is the process of discovering legal rules, legal principles, and legal doctrines in order to answer the legal questions faced. This paper is made with the problem of land dispute resolution and also the considerations and legal basis of judges in deciding cases. This study aims to resolve disputes. Legal approach, sources of legal materials include primary, secondary and tertiary data sources and normative research methods. The results of the study show how the dispute can occur because the defendants have taken over/taken over the disputed land of 12 HA. Therefore, the plaintiff filed a lawsuit against the defendants at the Ambon District Court. Article 171 of the Civil Code states that: Inheritance law is the law that regulates the transfer of ownership rights to inherited property from the testator then determines who is entitled to be the heir and determines how much each portion is, it is clear that by referring to the Civil Code it explains that everyone has the right to be an heir to every asset left by a subject who has a legal relationship that is legally family and/or property law which in essence has a close relationship between the testator and the intended heir.